The optimal training intervention for improving the change of direction performance of adolescent team-sport athletes: a systematic review and network meta-analysis - Yonghui Chen; Maiwulanjiang Tulhongjiang; Tianpeng Ling; Xinmiao Feng; Jing Mi; Ruidong Liu (PeerJ, 2025)
Background Due to the influence of growth, adolescent team-sport athletes have the need to improve their change of direction (COD) performance and reduce the risk of anterior cruciate ligament (ACL) injuries during COD. However, the optimal intervention for improving COD performance has not yet been determined. Objective To quantitatively assess the effects of diverse training interventions on COD performance. Methods A systematic search of five databases was conducted, adhering to the PRISMA guidelines. Randomized controlled trials that examined 10 distinct training interventions for COD performance in adolescent team-sport athletes were emphasized. Effect sizes were represented as standardized mean differences (SMD) with 95% credible intervals (CI). The Cochrane study risk assessment tool evaluated the risk of bias in the selected studies. Results Of the 36 studies analyzed, involving 1,125 participants. Eccentric overload training (EOT) (SMD = −2.06, 95% CI [−2.83 to −1.29]) emerged as the most effective training method for overall COD performance. Subgroup analysis shows that combined training (COM) (SMD = −2.14, 95% CI [−3.54 to −0.74]) was the best training intervention for COD performance with angles less than 90°. EOT (SMD = −2.84, 95% CI [−4.62 to −1.07]) also was two best training intervention for COD performance with angles greater than 90°. Conclusions The choice of training intervention should be determined based on the COD angle. When the COD angle exceeds 90° or is not restricted, EOT is the optimal intervention; however, this is not the case for angles below 90°. Further high-quality studies are needed in the future to validate these findings. Systematic review registration: PROSPERO CRD42024501819.